Do populist values or civic values drive support for referendums in Europe? - Bernhard Weßels; Richard Rose (European Journal of Political Research, 2021)
Representative democracy gives voters the right to influence who governs but its influence on policy making is only indirect. Free and fair referendums give voters the right to decide a policy directly. Elected representatives usually oppose referendums as redundant at best and as undermining their authority at worst. Democratic theorists tend to take electing representatives as normal and as normatively superior. The nominal association of popular decision making and populism has strengthened this negative view. Public opinion surveys show substantial support for holding referendums on important issues. Two major theories offer contrasting explanations for popular support for referendums; they reflect populist values or a commitment to the civic value of participation. This innovative paper tests an integrated model of both theories by the empirical analysis of a 17-country European survey. There is substantial support for all three civic hypotheses: referendum endorsement is positively influenced by attitudes towards participation, democratic ideals and whether elected representatives are perceived as responsive. By contrast, there is no support for populist hypotheses that the socioeconomically weak and excluded favour referendums and minimal support for the effect of extreme ideologies. The conclusion shows that most criticisms of referendums also apply to policy making by elected representatives. While referendums have limits on their use, there is a democratic argument for holding such ballots on major issues to see whether or not a majority of voters endorse the choice of their nominal representatives.
Keywords: 330; referendums; populism; participation; civic; democracy; elections